2007
DOI: 10.1590/s0074-02762007005000043
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine genetic polymorphism with hepatites B infection evolution in adult patients

Abstract: in a lower frequency in chronic patients than in individuals with P = 0.079; OR = 0.40;. In chronic patients with histological alterations it was not observed the genotype TGFB1+869 C/C, against 24.4% in the self limited infection group (100 versus 75.6%; P = 0.096; OR = 7.67; . Further studies in other populations, and evaluation of a greater number of individuals could contribute for a better understanding of the cytokine genetic polymorphism influence in HBV infection evolution. Key words: cytokine gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…Similarly, Ribeiro et al [66] studied the relationship between cytokine genetic polymorphisms and hepatitis B infection progression in a Brazilian population. However, this study found no definitive evidence pointing to the association of IL-6 -174 polymorphisms in the chronic HBV patient group versus the self-limited infection group.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…Similarly, Ribeiro et al [66] studied the relationship between cytokine genetic polymorphisms and hepatitis B infection progression in a Brazilian population. However, this study found no definitive evidence pointing to the association of IL-6 -174 polymorphisms in the chronic HBV patient group versus the self-limited infection group.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…In Brazil, there are only three studies evaluating cytokine gene polymorphisms in HBV infection [9,36]. One of them was performed in Recife [37] and determined the association between class II HLA alleles from HBV-infected blood samples; in this study, HBV infection was associated with HLA-DRB1*09 and DRB1*08 alleles, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al [36] analyzed cytokine genes polymorphisms in TNF-α (-308 G/A), TGFB1 (+869 T/C, +915 C/G), IL-10 (-1082 A/G, -819 T/C, -592 A/C), IL-6 (-174 C/G) and IFNG (+874 T/A) and found no differences between chronic HBV individuals and self-limited infection. Conde et al [9] also analyzed TNF-α 308 G/A, IFN-γ +874 T/A, TGF-β 1 509 C/T and IL-10 1082 A/G gene polymorphisms in chronic HBV-infected patients in order to find specific immunogenetic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these polymorphisms seem to be correlated to its production [18][19][20][21][22][23][24][25], and potentially conferring flexibility to immune response. The presence of certain genotypes may influence the course of both viral and bacterial infections [13,[26][27][28][29], as well as be associated to susceptibility or resistance to auto-immune diseases [30,31], or influence both solid organ post-transplant rejection processes [32,33], and graft versus host disease post bone-marrow transplantation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that immune response variations from polymorphisms *Address correspondence to this author at the Immunogenetics Lab, Clinical Analysis Department, Maringá State University, Maringá, Paraná, Brazil; E-mail: ramoliterno@uem.br and ramoliterno11@yahoo.com.br in regulatory regions of cytokine genes seem to influence the produced cytokine level and consequently the outbreak of different infectious disease, including Dengue Hemorrhagic Fever [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%